Spinal Cord Stimulation for Spasticity: Historical Approaches, Current Status, and Future Directions. Issue 4 (2nd April 2017) - Nagel, Sean J.; Wilson, Saul; Johnson, Michael D.; Machado, Andre; Frizon, Leonardo; Chardon, Matthieu K.; Reddy, Chandan G.; Gillies, George T.; Howard, Matthew A.
Abstract : Introduction: Millions of people worldwide suffer with spasticity related to irreversible damage to the brain or spinal cord. Typical antecedent events include stroke, traumatic brain injury, and spinal cord injury, although insidious onset is also common. Regardless of the cause, the resulting spasticity leads to years of disability and reduced quality of life. Many treatments are available to manage spasticity; yet each is fraught with drawbacks including incomplete response, high cost, limited duration, dose‐limiting side effects, and periodic maintenance. Spinal cord stimulation (SCS), a once promising therapy for spasticity, has largely been relegated to permanent experimental status. Methods: In this review, our goal is to document and critique the history and assess the development of SCS as a treatment of lower limb spasticity. By incorporating recent discoveries with the insights gained from the early pioneers in this field, we intend to lay the groundwork needed to propose testable hypotheses for future studies. Results: SCS has been tested in over 25 different conditions since a potentially beneficial effect was first reported in 1973. However, the lack of a fully formed understanding of the pathophysiology of spasticity, archaic study methodology, and the early technological limitations of implantable hardware limit the validity of many studies. SCS offers a measure of control for spasticity that cannot be duplicated with other interventions. Conclusions: With improved energy‐source miniaturization, tailored control algorithms, novel implant design, and a clearer picture of the pathophysiology of spasticity, we are poised to reintroduce and test SCS in this population.